Biological additives improved qualities, in vitro gas production kinetics, digestibility, and rumen fermentation characteristics of different varieties of rice straw silage - Ahmed, M. A.; Rafii, M. Y.; Nur Ain Izzati, M. Z.; Khalilah, A. K.; Awad, E. A.; Kaka, U.; Chukwu, S. C.; Liang, J. B.; Sazili, A. Q. (CSIRO Publishing, 2022)
Context: The amelioration of low-quality cheap feed for livestock production has become a huge challenge faced by the livestock producers coupled with the illicit disposal of the straw, which causes global environmental nuisance through burning and health impairment.